CONNOTATION OF FINANCIAL LITERACY ON FINANCIAL INCLUSION – A STUDY IN WEST GODAVARI DISTRICT (Journal of Pharmaceutical Negative Results, 2023)
Financial inclusion is aimed at providing affordable access to the financial services and products to the under privileged sections of the society so as to make them part of the formal financial sector. The success of financial inclusion is dependent on the awareness of these services to the people through financial literacy which is a set of skills which enable the people to effectively manage their financial resources through savings, financial planning, basics of banking, acquiring credit facilities and making the people financially smart. It is perceived that the financial literacy is vital in promoting financial inclusion, consumer protection and financial stability. All these go simultaneously which equips the people to understand the benefits of availing the financial services which are offered by the mainstream financial institutions. The present paper highlighted the need of financial inclusion along with the financial literacy for the people to have better utilization of the various schemes aimed at improving their financial status. A survey is conducted on 300 respondents in the district of West Godavari to understand the level of awareness and usage of the various banking operations. It is observed that there is significant relationship among the education levels and occupation with the level of awareness and accessing the financial services among the select respondents. The paper concluded with few suggestions for the betterment towards the usage and awareness of the financial services and products.